2017
DOI: 10.3390/rs9060558
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimized Endmember Extraction for Hyperspectral Image

Abstract: Endmember extraction (EE) is one of the most important issues in hyperspectral mixture analysis. It is also a challenging task due to the intrinsic complexity of remote sensing images and the lack of priori knowledge. In recent years, a number of EE methods have been developed, where several different optimization objectives have been proposed from different perspectives. In all of these methods, only one objective function has to be optimized, which represents a specific characteristic of endmembers. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Y and Y ˆ represent the original image and the reconstructed image, respectively. The abundance for reconstructing the image is calculated by the unconstrained least squares (UCLS) [52] using the following formulas: (6) where A is the endmember matrix, and S ˆ is the estimated abundance matrix.…”
Section: A Objective Functions Of Tseamentioning
confidence: 99%
See 1 more Smart Citation
“…Y and Y ˆ represent the original image and the reconstructed image, respectively. The abundance for reconstructing the image is calculated by the unconstrained least squares (UCLS) [52] using the following formulas: (6) where A is the endmember matrix, and S ˆ is the estimated abundance matrix.…”
Section: A Objective Functions Of Tseamentioning
confidence: 99%
“…To better suit real-world application, multi-objective EE was put forward to simultaneously optimize the two conflict objective functions, thus providing adjustable options to users. The multi-objective discrete particle swarm optimization algorithm (MODPSO) [52] was originally proposed to produce trade-off solutions between the reconstructed error and volume objective functions. Later on, several improved algorithms [53][54][55][56] were developed with the purpose of reaching a better Pareto front.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, refs. [18,22,[25][26][27]29] have turned to multiobjective optimization algorithms to optimize two indicators simultaneously, namely minimizing the RMSE and maximizing the volume.…”
Section: Intelligent-based Endmember Extraction Algorithmsmentioning
confidence: 99%
“…In order to alleviate the above problems, some intelligent optimization algorithms have been applied in endmember extraction in recent years. In the literature, the intelligent-based endmember extraction algorithms can be roughly divided into three main categories, which are the based on the genetic algorithms (GA) [17][18][19][20], the particle swarm optimization (PSO) algorithms [21][22][23][24][25][26][27] and the differential evolution (DE) algorithms [28,29]. Zhang et al [21] employed the discrete particle swarm optimization (DPSO) to minimize the root mean square error (RMSE) between the reconstructed image and the original image to obtain the appropriate endmember set by encoding each particle as the potential position of the active endmember in the hyperspectral image.…”
Section: Introductionmentioning
confidence: 99%
“…Another objective function used in the intelligent optimization-based methods is the maximization of the volume of the simplex constructed by the chosen endmembers. It has been shown that the EE results obtained by these two objective functions are different [38]. In order to get robust results for different real images, multiobjective optimization is used to simultaneously optimize the two objective functions [39], [40].…”
Section: Introductionmentioning
confidence: 99%